Knowledge on Fire : Attacks on Education in Afghanistan - World Bank (Washington, DC, 2013)
This study was conducted in a desire to better understand the nature of threats and attacks on education and offer recommendations for improving the ability of stakeholders to mitigate, and whenever possible, prevent, future attacks, with particular regard to the participation of communities in that process. Communities in Afghanistan are largely involved in the management and daily life of schools, as well as in their protection. Specifically, through an analysis of the nature of attacks and possible ways to mitigate risks by increased community involvement in protection of schools, the report seeks to contribute to: 1) increased security for students, teachers and other education personnel, 2) increased community involvement in and responsibility for school management, and 3) improved enrollment of students. Girls' education is clearly targeted more than boys; findings from this research indicate that the main perpetrators against the education of girls are the armed insurgency or internal community members. The roles that respondents see for the communities are numerous, and clearly defined by the nature of the attack and the perpetrators behind it. Additionally, involving the community from the very start of the school establishment process could be positive, both in ensuring community acceptance of the initiative, and in garnering their commitment to being involved in its protection.